A Scholar’s Guide to Research, Collaboration, and Publication in NINES - Nowviskie, Bethany (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2007)
AbstractThis essay offers a rationale for the design of Collex, the social software and faceted browsing system that powers NINES, a “networked infrastructure for nineteenth-century electronic scholarship.” It describes how Collex serves as a clearinghouse and collaborative hub for NINES, allowing scholars to search, browse, collect, and annotate digital objects relevant to nineteenth-century studies from a variety of peer-reviewed sources. It also looks forward to the next version of Collex, which will include a sophisticated exhibits builder, through which scholars can “remix” or re-purpose collected objects into annotated bibliographies, course syllabi, illustrated essays, and chronologies – and contribute these resources back into the NINES collective. A detailed guide to using Collex, complete with screenshots, is included. This article frequently links directly into the NINES system (in which, by virtue of its publication in Romanticism and Victorianism on the Net, it is already included), thereby gesturing at the future of networked, “born-digital” scholarship.